HUBUNGAN AMERIKA SERIKAT - TRANS PASIFIC PARTNERSHIP (TPP) DI MASA DONALD TRUMP STUDI KASUS: KELUARNYA AMERIKA SERIKAT DARI TRANS PASIFIC PARTNERSHIP (TPP) - Praditama, M Reza; Saeri, M. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research is a political economy study which describes the american interests left the tpp during the administration of Donald Trump. This research will focus on why America left the economy partnership. This study is interesting because it describes about a political economy policy who America President Donald Trump choose to make America great again. This is qualitative research which uses descriptive methods, and collected data from some resources like books, journals, official publications and its relevant websites. This paper uses the behavioralism perspective and International Treaty Theory. The object in this research is how a policy can make a different thing in a government. This agreement covers the entire trade sector ranging from trading and services, intellectual property rights, customs, and the cessation of the trade dispute. The result of this research shows that In its development, the Trans-Pacific Partnership has invited many criticisms from various parties in the countries involved. Many people think that TPP is only a tool for the United States to enter and dominate the economy in the region.Keywords: Partnership, Political Economy, Behavioralism, Policy